PT Vale's Security and Social Conflict Management Strategy in the Face of Land Disputes and Natural Resource Security Risks - Mukmin, Muhammad Aflahal (Journal of Public Representative and Society Provision, 2025)
In this study, attention is given to the strategies PT Vale Indonesia Tbk uses to handle security and conflict management when tackling land disputes and resource security problems in East Luwu, South Sulawesi. Even with protective measures set in place, such as security policies, forums, and CSR, disagreements remain between the company and local people. Combining Constructivism and the Right to Development, this study investigates the role of conflicts, which may not only be caused by weak laws or processes, but also by disagreements over meaning, old grievances, and beliefs of injustice. I conducted semi-structured interviews with leaders, NGO activists, people from PT Vale, and government officials, in addition to examining documents and paying attention during meetings and observational activities. It is shown that the strategies listed by PT Vale do not fully line up with the experiences of indigenous and local communities. A lot of people consider security to be suppressive, and many think that government engagement initiatives are not inclusive enough. It is often believed that CSR schemes are meant to balance things, rather than truly transform them. This research introduces the idea of corporate conflict management being grounded in norms and cultures, stressing the relevance of being legitimate, including everyone’s voice, and respecting cultural backgrounds. It states that the best way to resolve conflicts sustainably is to go from technocratic rule to shared governance and focusing on rights. If extractive activities are carried out without this transformation, they may keep causing resistance and unrest in East Luwu.